The Past and Future of Meaning - Jaroslav Peregrin (Baltic International Yearbook of Cognition, Logic and Communication, 2010)
For many centuries, a predominant view of meaning was that the meaning of a word is some kind of chunk of mind-stuff ("idea") glued to the word and animating it. However, while the traditional view was that we must first understand meaning, which enables us to understand language and hence our linguistic practices, a new approach to semantics that has emerged in the second half of the twentieth century, and which I see as marking the future of meaning, suggests that it is our linguistic practices on which we must concentrate from the beginning. In this paper I suggest a specific understanding of these practices, yielding the conclusion that meanings are reasonably seen as creatures of our activity of setting up certain systems of rules, thus opening up new kinds of virtual spaces which we can "enter". Meaning is what emerges within the intricately orchestrated space that we have somehow managed to bring into being by means of accepting the rules which are in charge of our language games, especially the game of giving and asking for reasons.